A test suite for analyzing the performance features of graphics processing units - Adinetz, A.V.; Shvets, P.A. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2011)
A test suite is proposed for graphics processors. These tests allow measuring various performance features, such as the delay and bandwidth of various types of memory, the efficiency of atomic operations, and the cache line size. With the aid of a specially developed memory test, we show that the coherency between threads has a much greater effect on the memory bandwidth than locality.